Evaluar el uso de la aplicación móvil para el sistema documental quipux utilizados en las empresas del cantón Montalvo. - Murillo Camacho, German Arturo (2023)
The purpose of this research is to evaluate the use of the mobile application for the Quipux document system in the companies of the Montalvo canton. This document system is an important tool for the handling and management of documentation in companies, and its mobile application allows quick and efficient access to information from anywhere. The objective of this research is to evaluate the level of adoption and effectiveness of the use of the Quipux mobile application in the document management of companies in Montalvo Canton, in order to identify its strengths, weaknesses and opportunities for improvement. To achieve this objective, various methods of analysis and explanation of the information will be used, such as literature review, statistical analysis and survey. The bibliographic review will make it possible to analyze the theoretical foundations of document management and the advantages of using mobile applications to improve the process. The statistical analysis will allow quantifying the use of the Quipux application in the companies of Canton Montalvo, identifying the main strengths and weaknesses of the system, and proposing solutions to improve its implementation. Likewise, the strengths and weaknesses of the Quipux application in terms of document management in the companies will be identified, and the opportunities for improvement that may exist will be evaluated. This will allow the establishment of specific recommendations to improve the efficiency and effectiveness of document management, and thus, increase productivity and business competitiveness.